Prerrequisitos cognitivos y su incidencia en el rendimiento académico del bloque de álgebra y funciones de la asignatura de matemática, de los estudiantes del octavo grado de educación general básica de la escuela de educación básica “18 de noviembre” de la ciudad de Loja, periodo académico 2018-2019. Lineamientos alternativos. - Elizalde Paredes, Edwin Fernando (2019)
The main goal of this research is to analyze the incidence of the cognitive prerequirements into the academic development in the algebra and functions in Mathematics in students of eight of basic education at “18 de Noviembre” elementary School, in the Loja City.The statement is based on the need of increasing and strengthen intellectual capacities of students since there is no emphasis in boosting the basic cognitive pre- requirements in the current educative process, it is mandatory to design strategies and techniques to contribute I to improve the teaching process. The hypothesis is stated as follows: the cognitive prerequirements highly influence in the academic performance of the algebra and functions unit in Mathematics in students of eight of basic education at “18 de Noviembre” academic year 2018-2019. There is applied the descriptive research; the used methodology to develop the methodological proposal starts from the analysis of the appliance of the evaluation of the cognitive-requirements and also from the academic performance test applied to the whole signed population of eigth grade academic year 2018- 2019, it considers 71 students and two teachers, so after that we apply scientific research techniques to gather information, the techniques are: interview, test and observation. To support the theory and to base the methodological proposal the bibliographic and electronic research was supported based on the settled goals.In summary the pre-requirements highly influence in the academic performance of students in algebra units in the Mathematics subject.This research is structured in the following order: problem statement; in the theoretical frame there is the scientific support of the importance of the cognitive pre- requirements since they highly influence at the time of improving skills and competences in students. As third aspect there are stated the analysis and interpret of results, finally there is settled the transformation proposal as an alternative guideline through catch up workshops aimed to improve basic topics before signing up for eight of basic education